Photochemical Tests on Leaves of Kapundung (Baccaurea Racemosa Muell.Arg) - Harahap, Susilawati; Harahap, Minah Iryanti; Harahap, Fitri Oma Ito; Harahap, Ichrima Askuri Nabella (PT Inovasi Pratama Internasional, 2025)
The Kapundung plant (Baccaurea Racemosa) has been used for traditional treatments like constipation, eye swelling, arthritis, abscesses, abdominal pain, and facilitating menstruation and urination. This study aims to examine flavonoids, tannins, phenolics, saponins, and alkaloids compounds in Kapundung Leaves. The research is a qualitative-experimental approach carried out by the maceration method and then identifying the chemical content of Kapundung leaves with phytochemical analysis tests in Institut Teknologi dan Kesehatan Sumatera Utara laboratory. The results of the phytochemical test of flavonoid compounds (marked by black colour) were carried out by adding a solution of FeCl31%; alkaloids (marked by black colour) carried out by adding HCl and Wagner's reagent; saponins (marked by the emergence of stable foam for 15 minutes) carried out by adding distilled water which was shaken vigorously and then allowed to stand for 15 minutes; tannins (marked by a blackish green colour) carried out with the addition of FeCl3, and phenolics (marked by black colour) carried out by adding distilled water and FeCl3 solution. Some activities widely used in the pharmaceutical sector such as flavonoids are used as antioxidants, tannins as antidiarrheals, saponins as foaming agents in shampoos, phenolics as antioxidants, and alkaloids as analgesics.